Генетична трансформація in planta м’якої пшениці з використанням штаму AGLO, який містить pBi2E з дволанцюговим РНК-супресором гена проліндегідрогенази - Воронова, С.С.; Бавол, А.В.; Дубровна, О.В. (Фактори експериментальної еволюції організмів, 2015)
Aims. The effectiveness of (Triticum aestivum L.) transformation in planta using strain AGLO harboring plasmid pBiОАТ with ornithine-aminotransferase gene and selective neomycin phosphotransferase II gene (nptII) has been analyzed. Methods. Agrobacterium-mediated genes transfer in planta during wheat pollination. Results. Seeds, RCR-analysis of which confirmed availability oat gene, of T1 - wheat’s plants have been obtained. Conclusions. It has been shown the possibility of stable integration of the transgenes at the wheat’s genome under Agrobacterium-mediated transformation in planta. Keywords: Triticum aestivum, Agrobacterium-mediated transformation in planta.